Deficiency of TREK-1 potassium channel exacerbates blood-brain barrier damage and neuroinflammation after intracerebral hemorrhage in mice - Yongkang Fang; Yeye Tian; Qibao Huang; Yue Wan; Li Xu; Wei Wang; Dengji Pan; Suiqiang Zhu; Minjie Xie (Journal of Neuroinflammation, 2019)
Abstract Background Intracerebral hemorrhage (ICH) is a devastating medical emergency with high mortality and severe neurological deficit. ICH-related poor outcomes are due to a combination of pathological processes that could be complicated by secondary insults. TWIK-related K+ channel 1 (TREK-1) is a two-pore-domain potassium channel that is highly expressed in the mammalian nervous system. Previous studies have shown that TREK-1 channels play important roles in various central nervous system diseases. However, its role in the secondary injuries after intracerebral hemorrhage remains unknown. In this study, we explored the function of TREK-1 in secondary blood-brain barrier injuries and neuroinflammation after intracerebral hemorrhage in mice. Methods Adult male TREK-1−/− mice and WT mice were subjected to a collagenase-induced ICH model. Immunostaining, western blot, and enzyme-linked immunosorbent assay were used to assess inflammatory infiltration and neuronal death. Blood-brain barrier compromise was assessed using electron microscopy and Evans Blue dye injection on days 1 and 3 after intracerebral hemorrhage. Magnetic resonance imaging and behavioral assessments were conducted to evaluate the neurologic damage and recovery after intracerebral hemorrhage. Results Genetic deficiency of TREK-1 channel exacerbated blood-brain barrier impairment and promoted cerebral edema after intracerebral hemorrhage. Meanwhile, TREK-1 deficiency aggravated focal inflammatory featured by the increased recruitment of microglia and neutrophils, the enhanced secretion of proinflammatory factors interleukin-1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), and cell adhesion molecules (CAMs). Furthermore, TREK-1 deficiency promoted neuronal injury and neurological impairment. Conclusions These results establish the first in vivo evidence for the protective role of TREK-1 in blood-brain barrier injury and neuroinflammation after intracerebral hemorrhage. TREK-1 may thereby be harnessed to a potential therapeutical target for the treatment of intracerebral hemorrhage.